Geomorphology and River Health in New South Wales : proceedings of a one day conference held at Macquarie University, October 7th, 1994 - Brierley, Gary J.; Nagel, Fiona (Australia : s.n., 1995)
"This book outlines geomorphic considerations for river management and a generic set of procedures, termed the River Styles framework, which provides a set of tools for interpreting river character, behavior, condition, and recovery potential. This book is essential reading for a wide range of river practitioners, including students, technical officers, consultants, and academics."--Jacket
Keywords: Rivers; Stream ecology; Geomorphology